Kripke's Critique of Descriptivism and the Conceptual Challenges of Necessity and Contingency - Souza, Euclides (Philosophy and Realistic Reflection, 2026)
This investigation offers a systematic critique of Saul Kripke's anti-descriptivist theory of rigid designation through five converging lines of argument, aiming to demonstrate that descriptive content is not merely auxiliary but philosophically necessary for reference. First, the analysis shows that Kripke's causal–historical model cannot function without informational elements that effectively operate as descriptions, thereby reintroducing the very resources it seeks to exclude. Second, it argues that rigid designation presupposes a stable criterion of identity across possible worlds, a requirement that cannot be satisfied without descriptive individuation. Third, Kripke's modal arguments concerning necessity and contingency are shown to depend implicitly on descriptive relations, particularly in cases involving mathematical necessity and essential properties. Fourth, the paper critiques Kripke's appeal to scientific essentialism, exposing the arbitrariness and contingency of the empirical criteria used to ground supposedly necessary identities. Finally, a contemporary challenge is introduced through the problem of declaration, which reveals that all speech acts are fundamentally performative and that the authority to fix reference depends on socially recognized declarative practices rather than on metaphysical discovery. Taken together, these arguments motivate an alternative framework—Declarative Descriptivism—according to which names require descriptive associations, not as fixed identificatory conditions, but as performatively constituted structures embedded in social and institutional practices. This proposal reframes the traditional debate between descriptivism and direct reference by shifting the focus from metaphysical grounding to the pragmatic and authoritative conditions under which reference is stabilized.